Elastography Evaluation of Benign Thyroid Nodules in Patients Affected by Hashimoto’s Thyroiditis - Carlo Cappelli; Ilenia Pirola; Elena Gandossi; Annamaria Formenti; Barbara Agosti; Maurizio Castellano (International Journal of Endocrinology)
The aim of the present prospective study was to evaluate the predictive value of elastography in benign thyroid nodules of patients affected by Hashimoto’s thyroiditis (HT). From January 2011 to January 2012, 242 nodules in patients affected by HT were submitted to fine needle aspiration cytology (FNAC). All of the patients underwent sonography and elastography performed before FNAC. 230 (95%) nodules were benign, 8 papillary cancers, and 4 follicular lesions. Score 1 was found in 79.1% of benign lesions (sensitivity 79.1%; specificity 66.7%; PPV 97.8%; NPV 14.3%; accuracy 78.5%; p<0.05). In order to evaluate the outcome of thyroid ultrasound echogenicity in relation to elastography features of nodule(s), all the patients with benign nodules were stratified according to their hypoechoic pattern of thyroid (mild-moderate and severe). Following stratification score 1 was found in 84.2% of benign nodules (sensitivity 75.0%; specificity 88.9%; PPV 27.3%; NPV 98.4%; accuracy 88.2%; p<0.0001) of patients with a mild-moderate ultrasound thyroid hypoechogenicity, whereas it was found in 60% of benign nodules (p=0.715) of patients with a marked thyroid hypoechogenicity. Elastography appears to have limited value in detecting thyroid cancer in patients affected by Hashimoto’s thyroiditis with severe hypoechoic thyroid tissue.